1999
DOI: 10.1523/jneurosci.19-15-06623.1999
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Emotional and Nonemotional Memories after their Reactivation: Role of β Adrenergic Receptors

Abstract: A memory trace in its active state is susceptible to interference by amnesic agents, such as hypothermia and electroconvulsive shock, and by NMDA receptor antagonists, suggesting that a time-dependent consolidation process occurs each time a memory is reactivated. The role of beta noradrenergic receptors in reconsolidation in rats was examined in both a positively reinforced radial maze task and a footshock-reinforced conditioned emotional response task. For the former, rats were trained over several days in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
316
9
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(357 citation statements)
references
References 35 publications
18
316
9
5
Order By: Relevance
“…That is, performance 1 week after treatment was still comparable to placebo. This is in contrast with our expectations based upon studies in which propranolol was found to affect post-retrieval processes like reconsolidation (Debiec & Ledoux, 2004;Miller et al, 2004;Przybyslawski et al, 1999). However, these studies used mostly fear conditioning paradigms, which are not directly comparable to our declarative memory task.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…That is, performance 1 week after treatment was still comparable to placebo. This is in contrast with our expectations based upon studies in which propranolol was found to affect post-retrieval processes like reconsolidation (Debiec & Ledoux, 2004;Miller et al, 2004;Przybyslawski et al, 1999). However, these studies used mostly fear conditioning paradigms, which are not directly comparable to our declarative memory task.…”
Section: Discussioncontrasting
confidence: 93%
“…This process is often referred to as reconsolidation (Debiec, Doyere, Nader, & LeDoux, 2006;Nader, Schafe, & Le Doux, 2000;Przybyslawski & Sara, 1997). Post-retrieval administration of propranolol has been found to disrupt spatial memory and inhibitory avoidance learning in rodents (Przybyslawski, Roullet, & Sara, 1999), as well as auditory fear conditioning (Debiec & Ledoux, 2004), and both findings have been explained in terms of impaired reconsolidation processes. Tronel and Alberini (2007) have recently shown that reconsolidation might also be dependent on the glucocorticoid system, as they found that a glucocorticoid receptor antagonist can disrupt conditioned fear in rats after reactivation of an inhibitory avoidance memory.…”
Section: Introductionmentioning
confidence: 99%
“…CREB-dependent transcription is required for cellular events underlying long-term memory in Aplysia, drosophila, mice, and rats (Impey et al, 1998;Lamprecht et al, 1997). Both the behavioral signs of fear freezing and the increase in P-CREB in the amygdala are sensitive to administration of b adrenergic antagonists (Przybyslawski et al, 1999). A cascade of intracellular events that culminate in increased intracellular [Ca 2+ ] or [cAMP] can lead to phosphorylation and activation of CREB (Lin et al, 1998;Takuma et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…If it would be possible to affect memory traces after they have been formed and retrieved, this could improve the treatment of stress-and memory-related disorders, like post traumatic stress disorder (PTSD) and phobias (de Quervain and Margraf 2008;Debiec and Ledoux 2006). Promising in this view is animal research that has shown that stress hormones like corticosterone (a glucocorticoid that resembles cortisol, but is naturally more abundantly present in rodents) and beta-adrenergic blocking agents like propranolol can affect long-term memory when administered during or after reactivation of the existing memory traces (Abrari et al 2008;Cai et al 2006;Debiec and Ledoux 2004;Maroun and Akirav 2007;Przybyslawski et al 1999;Tronel and Alberini 2007;Yang et al 2005). Processes that are thought to be influenced by these drugs are postretrieval mechanisms like extinction and reconsolidation (Suzuki et al 2004).…”
mentioning
confidence: 99%